BED PORTABLE MASSAGE OKSITOSIN TERHADAP KELANCARAN DAN PRODUKSI ASI PADA IBU POSTPARTUM - Metaliasari, Metaliasari; Septiani, Leri; Sastramihardja, Herri S; Sutisna, Ma’mun; Sugih, Siti; Rowawi, Roni (Poltekkes Kemenkes Bandung, 2025)
Breastfeeding remains a global challenge, with only 31 out of 194 countries successfully achieving the exclusive breastfeeding target of 50%. One effective method to improve breast milk flow and production is stimulating prolactin and oxytocin hormones through breast care, massage, and specifically oxytocin massage. Oxytocin massage has been recognized as an effective solution for addressing breastfeeding difficulties. This study aims to evaluate the effect of a portable oxytocin massage bed on breast milk flow and production in postpartum mothers. This research employed a quasi-experimental design with a non-equivalent control group approach. The study population consisted of postpartum mothers who gave birth between July 1 and July 30, 2024, for a total of 72 individuals. A sample of 60 participants was selected using accidental sampling and divided into two groups (intervention and control). Data collection was conducted through direct observation of postpartum mothers from day 1 to day 7, and the data were analyzed using a paired t-test. The results showed that the use of a portable oxytocin massage bed increased breastfeeding frequency (>8–12 times per day) with a p-value of 0.012 (<0.05), indicating a significant improvement. Additionally, after using the portable oxytocin massage bed, almost all respondents (28 out of 30) experienced full breast milk production, with a p-value of 0.001 (<0.05), demonstrating a significant effect on breast milk flow. Conclusion: The use of a portable oxytocin massage bed has a significant impact on improving breast milk flow and production in postpartum mothers.